Rethinking Support Policies: The Role of Belonging in Entrepreneurial Ecosystems - Alexandra David; Judith Terstriep; Jörg Freiling (International Migration, 2025)
This article explores the importance of belongingness in migrant entrepreneurs' (MEs) engagement within entrepreneurial ecosystems (EEs), focusing on emotional and social dimensions often overlooked in favour of structural factors. Through two case studies in Germany's Ruhr area, the article demonstrates how a strong sense of belonging enhances resilience, trust and social capital, essential for business success. The experiences of two MEs, Ilyas and Elif, illustrate belongingness as a catalyst for connectedness and embeddedness, enabling access to networks and resources while countering discrimination. The study suggests that policy frameworks should acknowledge and support the emotional and relational aspects of MEs' integration in EEs. Emphasising informal support systems, community engagement and tailored interventions could help overcome structural barriers and foster more inclusive ecosystems. Future research should further examine these dynamics across diverse cultural and geographical contexts to offer a more comprehensive understanding of MEs' entrepreneurial trajectories.
Keywords: 300; belongingness; connectedness; ecosystem integration; embeddedness; entrepreneurial ecosystems; migrant entrepreneurship